Recruitment and retention strategies for improving representation in clinical research: A meta-synthesis. - Carson J Peters; Joan M Greve; Arvin Karbasi; Michelle Walker; Luyi Adesanya; Joyonna Gamble-George; Nicole Redmond; Brenda Adjei; Olufunmilola Olufemi (PLoS ONE)
Objective To identify innovative strategies that may increase recruitment and/or retention of groups less represented in chronic disease clinical research. Methods A systematic review was conducted. Inclusion criteria were: (a) NIH-defined racial and ethnic minority groups and clinical research; (b) evidence-based, clinical research recruitment and/or retention strategies involving the leading causes of mortality and morbidity in the United States; (c) conducted in the United States; and (d) qualitative design. Data exploring the strategies were extracted and thematically analyzed. Results Twenty-seven studies were included. Studies focused on cancer (70%), recruitment (93%), and perspectives from clinicians (63%). The most referenced strategies were education (44%), communication (48%), and community-based participatory research (63%). Critical themes include empowerment, transparency, trust, and sustainability. Conclusions Strategies must prioritize the community and be implemented sustainably, where cultural humility and community-based participatory research are foundational.